(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2007)
Complicated, phasemanipulated by Barker code radiolocation signal is investigated. Results of calculation of correlation and crosscorrelation functions are obtained.